The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.2967/jnumed.108.055160
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Global and Regional Phase Analysis from Gated Myocardial Perfusion SPECT Imaging: Application to the Characterization of Ventricular Contraction in Patients with Left Bundle Branch Block

Abstract: Although many patients with heart failure benefit from cardiac resynchronization therapy (CRT), predicting which patients will respond to CRT remains challenging. Recent evidence suggests that the analysis of mechanical dyssynchrony using gated myocardial perfusion SPECT (MPS) may be an effective tool. The aim of this study was to evaluate global and regional gated MPS dyssynchrony measurements by comparing parameters obtained from patients with a low likelihood (LLk) of conduction abnormalities and coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…Particularly, observational trials have shown the significance of LV dyssynchrony for the prediction of response to CRT (6)(7)(8). LV dyssynchrony can be detected using different imaging modalities, including echocardiography with tissue Doppler imaging (TDI) (6)(7)(8) or strain (rate) imaging (11), MRI (12), and nuclear imaging with single photon emission computed tomography (SPECT) (13)(14)(15)(16)(17)(18). In particular, phase analysis on gated myocardial perfusion SPECT (GMPS) has been evaluated recently for the assessment of LV dyssynchrony (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Particularly, observational trials have shown the significance of LV dyssynchrony for the prediction of response to CRT (6)(7)(8). LV dyssynchrony can be detected using different imaging modalities, including echocardiography with tissue Doppler imaging (TDI) (6)(7)(8) or strain (rate) imaging (11), MRI (12), and nuclear imaging with single photon emission computed tomography (SPECT) (13)(14)(15)(16)(17)(18). In particular, phase analysis on gated myocardial perfusion SPECT (GMPS) has been evaluated recently for the assessment of LV dyssynchrony (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…We did find that our responder group had slightly lower phase entropy, which is a mathematic expression of synchrony not relying on phase similarity. Consequently, in contrast to phase bandwidth and SD (22), phase entropy is not influenced by boundary histogram bars-phase entropy is a reflection of the variability of synchrony during the ventricular contraction. O'Connell et al recently reported that LV entropy measurements in a gated blood-pool SPECT study were superior to phase SD for distinguishing healthy subjects from patients with LV aneurysm or diffuse or regional ventricular dysfunction (21).…”
Section: Phase Analysismentioning
confidence: 87%
“…A slightly different approach that imposes constant myocardial mass constraints was developed for Quantitative Gated SPECT (QGS) software, 15 the BW and SD measurements of which successfully separated normal patients from those with LBBB. 16 Correlations between phase parameters from GMPI SPECT and tissue Doppler were modest, …”
mentioning
confidence: 99%
“…A slightly different approach that imposes constant myocardial mass constraints was developed for Quantitative Gated SPECT (QGS) software, 15 the BW and SD measurements of which successfully separated normal patients from those with LBBB. 16 Correlations between phase parameters from GMPI SPECT and tissue Doppler were modest, partly because GMPI phase is a global measurement, while TDE represents single points and parameters. 17 GMPI phase SD and BW have the advantage of being highly reproducible and repeatable.…”
mentioning
confidence: 99%